Will livestock intensification help save Latin America's tropical forest? - Kaimowitz, D.; Angelsen, A. (2008)
Researchers have long argued that improved livestock technologies and intensification will reduce the pressure on Latin America's forests. This article combines economic theory with insights from seven case studies to examine under what conditions technological change will reduce (or increase) forest clearing. In many contexts improved technologies—by making cattle production more profitable—will result in more forest being converted to pasture. Silvopastoral systems and other labor-intensive practices can restrain pasture expansion, at least in the short-run. Unfortunately, in most cases ranchers will only be willing to adopt such land-saving practices when land has become scarce and most of the forest is gone.